Anxiety and affect in successful and less successful elite female basketball players: in-situ sampling before six consecutive games - Szabo, A.; Szucs, A.; Gáspár, Z.; Süle, K. (LASE Journal of Sport Science, 2014)
Justification and aim of the study: Successful athletes tend to approach contest situations with different psychological mindset than their less successful counterparts. The aim of this repeated-measures design study was to assess whether a successful (national league third rank) and a less successful (11th rank) first division women's basketball team differ inanxiety, positive affect, and negative affect before six consecutive games in the annual championship. Methods: Two psychometrically validated questionnaires, the Sport Competition Anxiety Test (SCAT; Martens et al., 1990) and the Positive Affect Negative Affect Scale (PANAS; Watson, Clark, & Tellegen, 1988) were used to measure pre-competitive anxiety and positive-and negative affect. The scales were completed by first division female basketball players, who were members of either the successful or the less successful team, before six matches; three played at home and three played away from home. Results: Successful players reported lower anxiety before games (effectsize (Cohen's d=1.2) than less success fulplayers. Both teams displayed more positive affect before the games played at home than before the games played away from home (d=.44) .How ever, ratings of the subjective states varied substantially across the games. Conclusion: The results, interpreted in light of an interactional model (Cerin et al., 2000), show that subjective appraisal of each competition situation yields very specific or unique expectations, which in turn determine the psychological states of the players before the upcoming contest.